Die Heidelbergse Kategismus en die kategesemateriaal van die Ned Geref. Kerk: 'n kerkhistoriese oorsig - J. M. van der Merwe (Acta Theologica)
In the year which we commemorate the 450th anniversary of the Heidelberg Catechism, this article follows the historical tracks of the catechism through the history of the Dutch Reformed Church with special focus on the role it played in the catechesis of the church. It starts with a short introduction about the origin of the Heidelberg Catechism. Secondly it gives an overview of the material used by the church through its early history before it compares the different books which were used later on. This is done in order to establish what role the Heidelberg Catechism played in the learning material of the church. The article concludes with the finding that the Heidelberg Catechism indeed played and still plays a huge role in the catechesis of the Dutch Reformed Church.